2019
DOI: 10.1038/s41598-018-38035-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of incidence and various demographic risk factors of traumatic humeral shaft fractures in China

Abstract: As a sub-study of the China National Fracture Study, this study aimed to better determine the incidence and risk factors of humeral shaft fracture in mainland China. We obtained all the data on humeral shaft fracture from the China National Fracture Study reported in 2017. Trained research teams personally interviewed all qualifying household members using a standardised questionnaire. A total of 512,187 (259649 boys and men, 252538 girls and women) questionnaires were collected and analysed from 112 neighbour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Meta-analysis of eight studies (10 study entries) 25 , 28 30 , 33 , 35 , 40 , 41 reporting on fracture risk at any anatomical site revealed a significant association between smoking and risk for any fracture (RR: 1.75; 95% CI: 1.10–2.80; p = 0.019; Fig. 2 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Meta-analysis of eight studies (10 study entries) 25 , 28 30 , 33 , 35 , 40 , 41 reporting on fracture risk at any anatomical site revealed a significant association between smoking and risk for any fracture (RR: 1.75; 95% CI: 1.10–2.80; p = 0.019; Fig. 2 ).…”
Section: Resultsmentioning
confidence: 97%
“…24 – 47 Mean NOS score for these studies was 6.9 ± 1.5 points. Six of these studies reported separate results for males and females, 26 , 28 , 30 , 31 , 46 , 47 one provided individual results for fractures at the trochanteric region and femoral neck, 32 and one study presented different results for fractures at any location and hip fractures. 33 The resulting meta-analysis thus comprised 32 study entries, involving 2,037,159 patients, of whom 518,995 (25.5%) were active smokers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Особливістю цих переломів є потенційний ризик пошкодження судинно-нервових утворень кістковими відламками, які зміщується під дією ретракції м'язів. Це може відбуватися під час безпосередньої травми, наданні першої медичної допомоги та на госпітальному етапі [4].…”
Section: вступunclassified